KAJIAN KUALITATIF KESEDIAAN GURU TADIKA SWASTA DALAM CABARAN MEMBIMBING PELAJAR DYSLEXIA: SATU KAJIAN KES DI KUALA SELANGOR (Proceedings of International Conference on Special Education, 2019)
In all levels of education, dyslexia is a commonly identified problem and has a significant percentage of the student population. The difficulty in mastering reading and writing skills among these children has led the private kindergarten teachers not able to equip them to a higher level as required in the National Pre-School Standard Curriculum. Therefore, the purpose of this study is to identify the readiness of private kindergarten teachers to teach student with dyslexia. The objectives of the study focused on teachers training, training needs for intervention programs and methods taken upon identifying children with reading and writing skills impairment. The study was conducted at Kuala Selangor, Selangor and participants were selected involving 10 kindergarten teachers from private kindergarten under the 550 Act. The data were collected using observation, interview and document analysis. Data were analyzed using descriptive and reference methods. Finding showed that private kindergarten teachers had no readiness to teach students with dyslexia and the methods of teaching the identified children with difficulty in reading and writing are varies as they had no proper training. The implication of the study showed that training of teachers in dyslexia are crucial. In conclusion, private kindergarten teachers should be trained systematically in teaching student with dyslexia for intervention program in the future.